2018
DOI: 10.1016/j.ijsu.2018.02.039
|View full text |Cite
|
Sign up to set email alerts
|

Tibial component sizing and alignment of TKR components does not significantly affect patient reported outcome measures at six months. A case series of 474 participants

Abstract: Tibial component sizing and alignment does not significantly affect short-term function, as measured by OKS, after total knee replacement. Dissatisfaction after TKR is likely due to other factors other than alignment of implant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 37 publications
(45 reference statements)
1
15
0
1
Order By: Relevance
“…Because an undersized baseplate will surely fit the tibial cut surface without any overhang but adversely induce insufficient interface coverage and potential malrotation. On the other hand, it is still unclear to what extent of tibial overhang will lead to clinical symptoms requiring revision surgery, some studies have found that sizing of the tibial components does not significantly affect postoperative outcomes, less than 3 mm of overhang were considered mild overhang and can be acceptable in some cases 2,6,10,[25][26][27][28] . Based on the above premises, both manual and automatic positioning for tibial baseplate has been reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…Because an undersized baseplate will surely fit the tibial cut surface without any overhang but adversely induce insufficient interface coverage and potential malrotation. On the other hand, it is still unclear to what extent of tibial overhang will lead to clinical symptoms requiring revision surgery, some studies have found that sizing of the tibial components does not significantly affect postoperative outcomes, less than 3 mm of overhang were considered mild overhang and can be acceptable in some cases 2,6,10,[25][26][27][28] . Based on the above premises, both manual and automatic positioning for tibial baseplate has been reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…2). According to previous studies, over-hang could be classified into three groups: anatomically sized, 0 mm ≤ distance < 1 mm; mild over-hang, 1 mm ≤ distance < 3 mm; severe overhang, distance ≥3 mm [11,12].…”
Section: Radiographic Measurementmentioning
confidence: 99%
“…For tibial component coverage, it is well known that tibial component over-hang causes soft tissue irritation, postoperative pain, limited knee flexion, and poor patient-reported outcome measures (PROMS) (the Knee Injury and Osteoarthritis Outcome score (KOOS score), the Knee Society score (KSS score), and the Western Ontario and McMaster Universities Osteoarthritis Index score (WOMAC)) [9,10]. However, some studies did not show the same results, and the effect of tibial component over-hang on postoperative PROMS is still under debate [11,12]. Many studies have shown that the tibial component under-hang can result in the sinking of the prosthesis and increase the risk of aseptic loosening [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive work has been undertaken to identify patient factors (e.g., male/female sex, co‐morbidities, mental health, and preoperative patient expectations) and surgical factors (e.g., implant design and surgical technique) that predict poor outcome following TKA. Increasingly, however, the role of patient biology as a potential driver of pain, stiffness and dissatisfaction is being considered …”
mentioning
confidence: 99%
“…1 While the majority of patients have a successful outcome, with reduced pain and improved function, 2 a significant proportion (10-20%) develop problems including joint stiffness, reduced range of knee motion and pain, which can ultimately require revision surgery. 3 Extensive work has been undertaken to identify patient factors (e.g., male/female sex, co-morbidities, mental health, and preoperative patient expectations) 4 and surgical factors (e.g., implant design and surgical technique) 5 that predict poor outcome following TKA. Increasingly, however, the role of patient biology as a potential driver of pain, stiffness and dissatisfaction is being considered.…”
mentioning
confidence: 99%